2002
DOI: 10.1021/ja017416c
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Cyclopropanation by Cyclocopolymerization of Butadiene

Abstract: An unprecedented cyclopropanation by cyclopolymerization reaction is presented. In particular, catalytic copolymerization processes of ethene and butadiene lead with high trans selectivity to a complete cyclocopolymerization of butadiene units. Ethene-based copolymers including cyclopropane and cyclopentane rings, which can be relevant to polyolefin applications, are obtained with high yields. Several aspects relative to the mechanism of this cyclocopolymerization reaction, including the high stereoselectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 21 publications
11
72
1
Order By: Relevance
“…The spectrum was analyzed with reference to the chemical shifts of the signals assigned to the vinyl groups, the cyclopropane skeleton, the cyclopentane skeleton, the 1,4-addition units and the 1,3-addition units in the ethylene/butadiene copolymers which were described in previous papers [8,18]. The determination of the butadiene content (1) and the vinyl groups content (2); the cyclopropane skeleton content (3); the cyclopentane skeleton content (4); the 1,4-addition units content (5) and the 1,3-addition units content (6) relative to all the butadiene-derived structural units was performed in accordance with the following Equations (1) to (6).…”
Section: Polymer Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…The spectrum was analyzed with reference to the chemical shifts of the signals assigned to the vinyl groups, the cyclopropane skeleton, the cyclopentane skeleton, the 1,4-addition units and the 1,3-addition units in the ethylene/butadiene copolymers which were described in previous papers [8,18]. The determination of the butadiene content (1) and the vinyl groups content (2); the cyclopropane skeleton content (3); the cyclopentane skeleton content (4); the 1,4-addition units content (5) and the 1,3-addition units content (6) relative to all the butadiene-derived structural units was performed in accordance with the following Equations (1) to (6).…”
Section: Polymer Characterizationmentioning
confidence: 98%
“…η2 primary coordination of butadiene leads to formation of vinyl groups or rings through a primary vinyl insertion, whereas η2 secondary and η4-cis coordination of butadiene leads to trans and cis 1,4-butadiene units through the formation of a syn-η3-coordinated growing chain and an anti-η3-coordinated growing chain, respectively [6][7][8][9]. Until now, reports on olefin/butadiene copolymerization, where the insertion reaction of the 1,3-butadiene proceeds via 1,2-insertion preferentially to form a vinyl group, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of butadiene leads in some cases to the presence of trans-vinylidene groups and trans-1, 2-cyclohexanediyl structures (237) and in others to trans-1,2-cyclopentanediyl and 1,2-cyclopropanediyl groups. (238). A diene such as 69, 70, or 71 (ethylidene norbornene, 1,4-hexadiene, and dicyclopentadiene, respectively) is copolymerized with ethylene and propylene to make EPDM rubber, a sulfur-vulcanizable elastomer.…”
Section: Dienesmentioning
confidence: 99%
“…The percent amounts of cyclic units (cyclopropane and cyclopentane) in the E-C3 polymers were calculated by 13 C NMR. The method is described in detail in Pragliola et al 8 …”
Section: Nmr Measurementsmentioning
confidence: 99%
“…[2][3][4][5][6][7] As it has been reported in the literature, PEs containing controlled amounts of methylene-1,2-cyclopropane and methylene-1,2-cyclopentane units (hereafter called E-C3) can be obtained by the polymerization of ethene with 1,3-butadiene using rac-[CH 2 (3-tert-butyl-1-indenyl) 2 ]ZrCl 2 activated by methylalluminoxane as a catalyst. [8][9][10][11][12] These PEs are technologically relevant because the presence of reactive cyclopropane rings in the chains discloses the possibility to obtain polymers with different properties. 13,14 For example, in a recent study by our group, we showed that it is possible to produce crosslinked PE by simple thermal treatments of E-C3 copolymers in the temperature range of 160-200 1C.…”
Section: Introductionmentioning
confidence: 99%